IMPROVING STUDENTS’ PROBLEM SOLVING ABILITIES THROUGH INQUIRY LEARNING MODELS - Nurmauli br Harianja (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This study aimed to improve students' problem solving ability. For this reason, teachers were required to create learning that accommodated the stages to achieve learning objectives in the form of drawing conclusions through hypotheses and data collection. One of the appropriate learning model for this purpose was inquiry learning. This study was conducted in class VI B SDN 9 Mandau. This study was conducted from March to April 2019. The method of this study was classroom action research including the stages of planning, implementation, observation, and reflection. The instrument used in this study was observation sheets. The results revealed that the students’ problem solving ability in the first cycle was 73.37 and the total classical completeness was 62.96%, in which only 17 students reached the KKM. In cycle II, the students' problem solving ability reached 81.01 and the total classical completeness was 92.59%, meaning that 25 students reached the predetermined KKM. Based on the results of the study, it was concluded that inquiry learning model improved the students’ problem solving abilities at grade VI B grade of SDN 9 Mandau.